Type 2 diabetes in Vietnam: a cross-sectional, prevalence-based cost-of-illness study - Le NTD (Dove Medical Press, 2017)
Nguyen Tu Dang Le, Luyen Dinh Pham, Trung Quang Vo Department of Pharmacy Administration, Faculty of Pharmacy, University of Medicine and Pharmacy at Ho Chi Minh City, Vietnam Background: According to the International Diabetes Federation, total global health care expenditures for diabetes tripled between 2003 and 2013 because of increases in the number of people with diabetes as well as in the average expenditures per patient. This study aims to provide accurate and timely information about the economic impacts of type 2 diabetes mellitus (T2DM) in Vietnam. Method: The cost-of-illness estimates followed a prospective, prevalence-based approach from the societal perspective of T2DM with 392 selected diabetic patients who received treatment from a public hospital in Ho Chi Minh City, Vietnam, during the 2016 fiscal year. Results: In this study, the annual cost per patient estimate was US $246.10 (95% CI 228.3, 267.2) for 392 patients, which accounted for about 12% (95% CI 11, 13) of the gross domestic product per capita in 2017. That includes US $127.30, US $34.40 and US $84.40 for direct medical costs, direct nonmedical expenditures, and indirect costs, respectively. The cost of pharmaceuticals accounted for the bulk of total expenditures in our study (27.5% of total costs and 53.2% of direct medical costs). A bootstrap analysis showed that female patients had a higher cost of treatment than men at US $48.90 (95% CI 3.1, 95.0); those who received insulin and oral antidiabetics (OAD) also had a statistically significant higher cost of treatment compared to those receiving OAD, US $445.90 (95% CI 181.2, 690.6). The Gradient Boosting Regression (Ensemble method) and Lasso Regression (Generalized Linear Models) were determined to be the best models to predict the cost of T2DM (R2=65.3, mean square error [MSE]=0.94; and R2=64.75, MSE=0.96, respectively). Conclusion: The findings of this study serve as a reference for policy decision making in diabetes management as well as adjustment of costs for patients in order to reduce the economic impact of the disease. Keywords: cost-of-illness, diabetes mellitus, hospital, Vietnam